Mixed oligopoly, public firm behavior, and free private entry - Bennett, John; La Manna, Manfredi (Economics letters, 2012)
We analyze a mixed oligopoly with free entry by private firms, assuming that a public firm maximizes an increasing function of output, subject to a break-even constraint. We establish an irrelevance result: whenever a mixed oligopoly is viable, then aggregate output, aggregate costs and welfare are the same with and without the public firm. However, replacing a viable mixed oligopoly with a public monopoly yields higher net welfare. Implications for privatization policy are suggested. ► When a public firm is profit-constrained, its objective function is immaterial as long as it is increasing in the firm’s output. ► If a mixed oligopoly is viable under free entry, then it yields the same net social welfare as a free-entry all-private oligopoly. ► If a mixed oligopoly is viable under free entry, then a monopoly public firm yields strictly higher net social welfare.